The reliability and validity of the Complex Task Performance Assessment: A performance-based assessment of executive function. Issue 5 (4th July 2017) - Wolf, Timothy J.; Dahl, Abigail; Auen, Colleen; Doherty, Meghan
Abstract : The objective of this study was to evaluate the inter-rater reliability, test-retest reliability, concurrent validity, and discriminant validity of the Complex Task Performance Assessment (CTPA): an ecologically valid performance-based assessment of executive function. Community control participants ( n = 20) and individuals with mild stroke ( n = 14) participated in this study. All participants completed the CTPA and a battery of cognitive assessments at initial testing. The control participants completed the CTPA at two different times one week apart. The intra-class correlation coefficient (ICC) for inter-rater reliability for the total score on the CTPA was .991. The ICCs for all of the sub-scores of the CTPA were also high (.889–.977). The CTPA total score was significantly correlated to Condition 4 of the DKEFS Color-Word Interference Test ( p = −.425), and the Wechsler Test of Adult Reading ( p = −.493). Finally, there were significant differences between control subjects and individuals with mild stroke on the total score of the CTPA ( p = .007) and all sub-scores except interpretation failures and total items incorrect. These results are also consistent with other current executive function performance-based assessments and indicate that the CTPA is a reliable and valid performance-based measure of executive function.